Prevalence and associated factors of low serum zinc concentration in adolescents of Gambella city, Southwest Ethiopia - Megersa DG; Mekonnen Abebe S; Abebe FM; Wassie MM (Nutrition and Dietary Supplements, 2017)
Dedessa Gemeda Megersa,1 Solomon Mekonnen Abebe,2 Fikru Mekonnen Abebe,3 Molla Mesele Wassie2 1Department of Clinical Nursing, Gambella Teachers’ Education and Health Science College, Gambella, 2Human Nutrition Department, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, 3Department of Plant Science, College of Agriculture, Wollo University, Dessie, Ethiopia Background: Zinc deficiency is a major public health problem in many developing countries. It has been linked with reduced growth and development in adolescents. The deficiency increases vulnerability to infections, immune dysfunction, hypogonadism, and abnormal neurosensory changes. However, this problem has not received due attention, especially in Ethiopia. Therefore, this study is aimed to assess the prevalence and factors associated with low serum zinc concentration in high school adolescents of Gambella city, Southwest Ethiopia. Methods: An institution-based cross-sectional study was conducted in Gambella city in April 2015. A total of 346 high school adolescents were randomly selected and invited to participate in the study. Data were gathered using a structured questionnaire after obtaining a written consent and assent. The concentration of zinc in serum was measured by atomic absorption spectrometry. Logistic regression was used for statistical analysis. Results: Three-hundred and two high school adolescents were included in the study, with a response rate of 87.3%. The mean (± standard deviation [SD]) age of the respondents was 17 (±1) years. The mean (±SD) serum zinc concentration of the respondents was 134.1 (±48) µg/dL, while the prevalence of low serum zinc concentration was 9.6% (95% confidence interval [CI]: 6.3–12.9). The prevalence of low serum zinc concentration was 11.2% (95% CI: 5.9–16.4) in females and 8.2% (95% CI: 3.9–12.5) in males. Frequency of malaria attack in the last 2 weeks preceding the study (adjusted odds ratio [AOR]=4.12; 95% CI: 1.58–10.66), increased physical activity (AOR=1.97; 95% CI: 1.43–6.39), low dietary diversity scores (AOR=4.23; 95% CI: 1.52–12.29), poor wealth status (AOR=4.68; 95% CI: 1.41–9.49), and being stunted (AOR=2.84; 95% CI: 1.29–7.46) were significantly associated with low serum zinc concentration. Conclusion: The prevalence of low serum zinc concentration was not high in the study population. The frequency of malaria attacks in the last 2 weeks, physical activity, low dietary diversity, poor wealth status, and being stunted were associated with low serum zinc concentration. Developing strategies to prevent malaria infection, enhancing physical activities, and optimizing dietary diversity scores are recommended to improve the serum zinc concentrations of adolescents. Keywords: adolescents, zinc deficiency, serum zinc concentration, Ethiopia